DIMENSI SUFISTIK PUISI-PUISI SAPARDI DJOKO DAMONO - Nurefendi Fradana, Ahmad (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
The main purpose of this research is to reveal mystical aspects within Sapardi Djoko Darmono’s poetries found in “Hujan Bulan Juni” poetry collection. Those poetries are “Sajak Desember”, “Dalam Doaku”, “Berjalan ke Barat Waktu Pagi Hari”, “Dalam Diriku”, “Hujan Bulan Juni”, “Aku Ingin”, and “Ajaran Hidup”. This research applied qualitative method of analysis with semiotic approach. Applying semiotic approach, the researcher searched for what is considered as the main markers/ signs of the poetries, analyzed the words which are used denotatively and connotatively, run paradigmatic analysis, and conducted syntagmatic analysis to discover mystical aspects within the poetries. Life lessons that can be taken from Sapardi Djoko Darmono’s mystical poetries is that life in this world is just temporary. There is still more immortal life that is life after death. Resignation to Allah swt, the almighty God, can be done by repenting totally only to Allah, being conscious of errors and mistakes while asking for mercies.